СЕТЕВОЕ ОБРАЗОВАНИЕ В ВУЗЕ: МЕДИЦИНСКАЯ ТЕРМИНОЛОГИЯ РУССКОГО ЯЗЫКА - Абдуллаева, Р.М. (SCIENCE and SOCIETY, 2020)
The article discusses the role of network education in the process of teaching Russian as a foreign language. The network information space has practically covered all spheres of human activity and society and continues to be introduced into everyday life in a variety of ways.
Keywords: Russian language; learning process; Internet; networking technology; computer; terminology; vocabulary; situational context